Markers of early renal changes induced by industrial pollutants. II. Application to workers exposed to lead. Issue 1 (January 1993) - Cárdenas, A; Roels, H; Bernard, A M; Barbon, R; Buchet, J P; Lauwerys, R R; Roselló, J; Ramis, I; Mutti, A; Franchini, I
Abstract : The present study has been carried out in the framework of a collaborative research project on the development of new markers of nephrotoxicity. A battery of more than 20 potential indicators of renal changes has been applied to 50 workers exposed to lead (Pb) and 50 control subjects. After application of selection criteria 41 exposed and 41 control workers were eventually retained for the final statistical analysis. The average blood Pb concentration of exposed workers was 480 micrograms/l and their mean duration of exposure was 14 years. The battery of tests included parameters capable of detecting functional deficits (for example, urinary proteins of low or high molecular weight), biochemical alterations (for example, urinary eicosanoids, glycosaminoglycans, sialic acid) or cell damage (for example, urinary tubular antigens or enzymes) at different sites of the nephron or the kidney. The most outstanding effect found in workers exposed to Pb was an interference with the renal synthesis of eicosanoids, resulting in lower urinary excretion of 6-keto-PGF1 alpha and an enhanced excretion of thromboxane (TXB2). The health significance of these biochemical alterations, detectable at low exposure to Pb is unknown. As they were not associated with any sign of renal dysfunction, they may represent reversible biochemical effects or only contribute to the degradation of the renal function from the onset of clinical Pb nephropathy. The urinary excretion of some tubular antigens was also positively associated with duration of exposure to Pb. Another effect of Pb that might deserve further study is a significant increase in urinary sialic acid concentration.